Composition for sustained-release material
The composition of a temperature-sensitive polymer, anionic polymer, and water-soluble compound addresses the challenge of maintaining consistent active ingredient release by thickening at body temperature and sustaining release stability.
Patent Information
- Application Number
- JP2024157121
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-28
AI Technical Summary
Conventional sustained release materials struggle to maintain a consistent release rate of active ingredients over a long period, failing to adequately thicken at the application site and maintain stability.
A composition comprising a temperature-sensitive polymer, a polymer compound with anionic groups, and a water-soluble compound, where the weight ratio of anionic groups to the water-soluble compound is between 0.025 and 20, allowing the composition to thicken at body temperature and sustain the release of the active ingredient.
The composition effectively thickens at body temperature, maintaining the active ingredient at the application site and ensuring a stable, long-term release with minimal change in release rate, thus enhancing sustained release stability.
Smart Images

Figure 2025043311000001 
Figure 2025043311000002 
Figure 2025043311000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for sustained release materials. [Background technology]
[0002] Sustained-release materials that are placed at the application site (for example, in the oral cavity or on the skin) to gradually release an active ingredient and sustain the effect of the active ingredient have been studied (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 57-118511 Summary of the Invention [Problem to be solved by the invention]
[0004] Sustained-release materials are required to remain at the site of placement and release active ingredients for an extended period of time, as well as to minimize changes in the release rate of the active ingredients over that period of time. However, conventional technology has not been able to adequately resolve these issues, and improvements have been required.
[0005] The object of the present invention is to provide a composition that can thicken a composition containing an active ingredient, retain it at the application site, release the active ingredient for a long period of time after thickening, and reduce changes in the release rate of the active ingredient (excellent sustained release stability). [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention is as follows. [1] A composition for sustained release material comprising a temperature-sensitive polymer (X), a polymeric compound (Y) having an anionic group, and a water-soluble compound (Z) having a number average molecular weight of 100 to 15,000, wherein the ratio (Wy / Wz) of the weight Wy of the polymeric compound (Y) having an anionic group to the weight Wz of the water-soluble compound (Z) is 0.025 to 20. [2] The composition for sustained release material according to [1], wherein the temperature-sensitive polymer (X) is at least one member selected from the group consisting of N-isopropylacrylamide polymers, methylcellulose and hydroxyalkylmethylcellulose. [3] The composition for sustained release materials according to [1] or [2], wherein the ratio [Wx / (Wy+Wz)] of the weight Wx of the temperature-sensitive polymer (X) to the total weight of the weight Wy and the weight Wz is 0.08 to 45. Effect of the Invention
[0007] According to the present invention, it is possible to provide a composition that thickens a composition containing an active ingredient, retains the active ingredient at the application site, and releases the active ingredient for a long period of time after thickening, while minimizing changes in the release rate of the active ingredient (excellent sustained release stability). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The composition for sustained release material of the present invention is a composition comprising a temperature-sensitive polymer (X), a polymeric compound (Y) having an anionic group, and a water-soluble compound (Z) having a number average molecular weight of 100 to 15,000, wherein the ratio (Wy / Wz) of the weight Wy of the polymeric compound (Y) having an anionic group to the weight Wz of the water-soluble compound (Z) is 0.025 to 20.
[0009] The temperature-sensitive polymer (X) is a component that does not easily increase viscosity at room temperature (e.g., 25°C) or below, but has the effect of increasing viscosity by reacting with a polymer compound (Y) having an anionic group at temperatures higher than room temperature. Hereinafter, "increasing viscosity" is also referred to as "thickening." In this specification, "temperature-sensitive polymer (X)" may be referred to as "polymer (X)."
[0010] Examples of the temperature-sensitive polymer (X) include N-isopropylacrylamide polymer, methylcellulose, and hydroxyalkylmethylcellulose. Among these, from the viewpoint of storage stability of the composition, N-isopropylacrylamide polymer and hydroxyalkylmethylcellulose are preferred, hydroxypropylmethylcellulose is more preferred, and hydroxypropylmethylcellulose having 0.1 to 0.25 moles of hydroxypropyl groups per molecule is even more preferred. The temperature-sensitive polymer (X) may be used alone or in combination of two or more kinds. The (weight or number) average molecular weight of the temperature-sensitive polymer (X) is preferably 100,000 to 300,000.
[0011] The polymer compound (Y) having an anionic group is a component that can act on the polymer (X) to promote an increase in the viscosity of the composition at temperatures around body temperature (for example, 35° C. to 42° C.). Examples of the polymer compound (Y) having an anionic group include polymers having one or more groups selected from carboxy groups and carboxylate groups, and specific examples include sodium carboxymethylcellulose, sodium poly(meth)acrylate, xanthan gum, and sodium alginate. Among these, from the viewpoint of promoting the increase in viscosity of the composition at temperatures around body temperature, sodium carboxymethylcellulose, sodium polyacrylate, xanthan gum, and sodium alginate are preferred, and carboxymethylcellulose and xanthan gum are more preferred. The polymer compound (Y) may be used alone or in combination of two or more. The weight average molecular weight of the polymer compound (Y) having an anionic group is preferably 50,000 to 3,000,000, and more preferably 100,000 to 2,000,000. In this specification, the "polymer compound (Y) having an anionic group" may be referred to as the "polymer compound (Y)".
[0012] The water-soluble compound (Z) having a number average molecular weight of 100 to 15,000 is an ingredient that can function as an active ingredient in the composition of the present invention. In the present invention, water-soluble means that the solubility in 100 g of water is 1 g or more (20°C). In the present invention, the number average molecular weight of the water-soluble compound (Z) is 100 to 15,000. In this specification, the "water-soluble compound (Z) having a number average molecular weight of 100 to 15,000" may be referred to as the "water-soluble compound (Z)" or the "compound (Z)".
[0013] In the present invention, the number average molecular weight means the chemical formula weight of a compound in the case of a single compound, and can be calculated from the structural formula. In the case of a compound having a molecular weight distribution, such as a high molecular weight polymer, the number average molecular weight is a value calculated from the average degree of polymerization.
[0014] Examples of the compound (Z) include polymerized phosphoric acid, tungstic acid (H2WO4), ethylenediaminetetraacetic acid, glutamic acid, iminodiacetic acid, malic acid, citric acid, tartaric acid, adenosine triphosphate, guanosine triphosphate, and salts thereof. Examples of the polymerized phosphoric acid include polyphosphoric acid (linear) and metaphosphoric acid (cyclic). Examples of the polyphosphoric acid include those having a repeating number (chain length) of phosphoric acid units of 2 to 150.
[0015] Examples of the salt include inorganic acid salts such as hydrochloride, sulfate, nitrate, and phosphate; organic acid salts such as acetate, citrate, maleate, malate, oxalate, lactate, succinate, fumarate, and propionate; alkali metal salts such as sodium salt and potassium salt; alkaline earth metal salts such as calcium salt and magnesium salt; ammonium salt; salts with organic bases such as triethylamine, triethanolamine, and pyridine; amino acid salts with basic or acidic amino acids such as arginine and glutamic acid. Among these, sodium salt and potassium salt are preferred. All of the compounds exemplified above are water-soluble.
[0016] From the viewpoint of sustained release stability, the compound (Z) is preferably citric acid, malic acid, glutamic acid, pentasodium triphosphate, sodium hexametaphosphate, sodium pentapolyphosphate, or sodium polyphosphate having a chain length of 5 to 130. The compound (Z) can be used alone or in combination of two or more kinds.
[0017] In the composition of the present invention, the ratio (Wy / Wz) of the weight Wy of the polymer compound (Y) having an anionic group to the weight Wz of the water-soluble compound (Z) is 0.025 to 20. By having the weight ratio (Wy / Wz) within the above range, the active ingredient can be released for a long period of time at a temperature near body temperature, and the composition can have excellent sustained release stability. From the viewpoint of sustained release stability, the weight ratio (Wy / Wz) is preferably 0.03 to 15, more preferably 0.03 to 10.
[0018] In the composition of the present invention, the ratio [Wx / (Wy+Wz)] of the weight Wx of the temperature-sensitive polymer (X) to the total weight (Wy+Wz) of the weight Wy of the polymer compound and the weight Wz of the water-soluble compound is preferably 0.08 to 45, more preferably 0.1 to 10, and even more preferably 0.1 to 5, from the viewpoint of sustained release stability.
[0019] The composition for sustained-release materials of the present invention contains a temperature-sensitive polymer (X), a polymer compound (Y) having an anionic group, and a water-soluble compound (Z). When these three components are mixed with water, they are unlikely to thicken at room temperature (e.g., 25°C) or lower, but the viscosity begins to increase rapidly at temperatures near body temperature (35°C to 42°C), and the composition can remain at the application site within several minutes (3 to 10 minutes), and thickens to a viscosity that allows the active ingredient to be sustainedly released for a long period of time. The composition for sustained-release material of the present invention may be in an embodiment that contains water in addition to the above three components, or may be in an embodiment that contains water before use.
[0020] When the composition for sustained release material of the present invention contains water, the weight ratio of the anionic polymer (Y) is preferably 0.1 to 2% by weight based on the weight of the composition for sustained release material. By having the weight ratio of the polymer compound (Y) within the above range, the composition can be thickened within a few minutes (for example, within 3 to 10 minutes) at a temperature near body temperature, retained at the application site, and the effect of releasing a predetermined amount of the active ingredient [compound (Z)] for a long time (sustained release stability) can be improved. From the viewpoint of thickening the composition at a temperature near body temperature, the weight ratio of the polymer compound (Y) is more preferably 0.5% by weight or more, and even more preferably 1% by weight or more.
[0021] When the composition for sustained release materials of the present invention contains water, the weight ratio of the water-soluble compound (Z) is preferably 0.01 to 4% by weight based on the weight of the composition for sustained release materials. By having the weight ratio of the compound (Z) within the above range, the effect of the compound (Z) is more easily manifested, and the effect of thickening the composition for sustained release materials within a few minutes (for example, within 3 to 10 minutes) at a temperature around body temperature is more easily manifested. From the viewpoint of manifestation of the effect of the compound (Z) and thickening of the composition at a temperature around body temperature, the weight ratio of the compound (Z) is more preferably 0.1% by weight or more, and even more preferably 1% by weight or more.
[0022] When the composition for sustained release materials of the present invention contains water, the weight proportion of the temperature-sensitive polymer (X) is preferably 0.5 to 5 wt %, more preferably 1 to 2 wt %, based on the weight of the composition for sustained release materials, from the viewpoint of thickening the composition for sustained release materials at temperatures around body temperature.
[0023] When the composition for sustained release materials of the present invention contains water, the weight proportion of water is preferably 85 to 97% by weight based on the weight of the composition for sustained release materials, from the viewpoint of mixability when producing the composition.
[0024] The composition for sustained release material of the present invention may contain a component that adjusts the liquidity of the composition to neutral, in addition to the temperature-sensitive polymer (X), the polymer compound (Y) having an anionic group, the water-soluble compound (Z) and water. Examples of the component that adjusts the liquidity include ammonia water and citric acid monohydrate. When a component for adjusting the liquidity is used, the amount used is preferably 0.01 to 3 wt %, more preferably 0.1 to 2.7 wt %, based on the weight of the composition for sustained-release materials.
[0025] The composition for sustained release material of the present invention may contain other components other than the temperature-sensitive polymer (X), the polymer compound (Y) having an anionic group, the water-soluble compound (Z), water, and the component for adjusting liquidity. The other components include lubricants such as wax, antioxidants, ultraviolet absorbers, defoamers, preservatives, fragrances, solvents [water and organic solvents (ethanol, etc.)], etc. When other components are used, the amount of the other components used is preferably 2% by weight or less based on the weight of the composition for sustained release material.
[0026] When the composition for sustained-release materials of the present invention contains water, it is preferable that the viscosity at 25° C. measured with a cone-plate type rotational viscometer is 100 to 200 Pa·s, from the viewpoint of ease of placement at the application site. Specifically, the viscosity is measured by the following measurement method. (Measurement conditions) Equipment: MCR92 (Anton Paar) Fixture: PP-25 (parallel plate with a diameter of 25 mm) Gap: 1mm ·Temperature: 25℃, -Distortion rate: 0.1 1 / s (Rotation speed: 0.11 rpm) (Measurement method) Approximately 1.0 g of the composition prepared is placed on the sample stage and sandwiched with PP-25. The parallel plates are spaced 1 mm apart, and any excess sample is scraped off. After regulating the temperature at 25°C for 1 minute, the viscosity value at a rotation speed of 0.11 rpm is recorded.
[0027] The composition for sustained release material of the present invention can be produced by blending the respective components and mixing them at room temperature. The blending order and blending method of the respective components are not particularly limited.
[0028] From the viewpoint of mixability during the production of the composition, the viscosity of a 1 wt % aqueous solution of the temperature-sensitive polymer (X) at 25° C. is preferably 100 mPa·s to 10,000 mPa·s. The viscosity can be measured using the device used for measuring the viscosity of the composition for sustained release material described above.
[0029] From the viewpoint of mixability during the production of the composition, the viscosity of a 1 wt % aqueous solution of the polymer compound (Y) having an anionic group at 25° C. is preferably 500 mPa·s to 10,000 mPa·s. The viscosity can be measured using the device used for measuring the viscosity of the composition for sustained release material described above.
[0030] [How to use] The composition for sustained-release materials of the present invention can be applied to a selected site and by a selected method (eg, application, pasting) depending on the effect of the water-soluble compound (Z) contained in the composition. An example of a method for using the composition for sustained-release materials of the present invention will be described below. The sustained-release material composition of the present invention can be used by applying it directly, or after incorporating water as necessary, to the application site [e.g., mucous membranes {oral cavity (tongue, gums, gingiva, etc.), intestines, eyes, etc.}, skin, nails (nail plates), etc., and the surrounding areas] with a finger or the like, and placing the composition on the affected area. For example, when the composition for sustained-release materials of the present invention is applied to the mucous membranes of the oral cavity (tongue, gums, gingiva, etc.), it is expected to have the effect of sustained release of the encapsulated active ingredient for a long period of time. Specific examples of applications in such cases include toothpastes, oral gels, oral care foods, supplements, pet care products, and nail care products. The sustained release material composition of the present invention can also be used as a medicine, medical device (medical adhesive, wound healing material, etc.), quasi-drug, cosmetic, food, etc., by using a water-soluble compound (Z) according to the desired effect.
[0031] [Effects] The effects of the present invention will now be described. The three components contained in the composition for sustained-release materials of the present invention [temperature-sensitive polymer (X), polymer compound (Y) having an anionic group, and water-soluble compound (Z)] are unlikely to thicken at room temperature (e.g., 25°C) or lower when water is added. However, when the three components are added with water, the viscosity begins to increase rapidly at temperatures near body temperature (35°C to 42°C), and the composition can remain at the application site within several minutes (3 to 10 minutes), and has the property of thickening to a viscosity that allows the active ingredient to be sustainedly released for a long period of time. Although the details of the mechanism by which such properties are expressed are unknown, it is speculated as follows. The temperature-sensitive polymer (X) contained in the composition of the present invention has the effect of not increasing the viscosity of the composition at room temperature or below, but increasing the viscosity of the composition at temperatures higher than room temperature. The composition for sustained release material of the present invention is not likely to thicken at room temperature or below due to the action of the temperature-sensitive polymer (X), but when the temperature of the composition rises to a temperature near body temperature (higher than room temperature), the anionic group of the polymer compound (Y) reacts with the temperature-sensitive polymer (X), and the viscosity of the composition begins to increase. The polymer compound (Y) and the water-soluble compound (Z) contained in the composition of the present invention together with the temperature-sensitive polymer (X) are each in a specific amount, so it is presumed that they interact with each other to make it possible to keep the viscosity of the composition at a temperature near body temperature at the application site and to thicken it to a viscosity that allows sustained release of the active ingredient.
[0032] When the composition of the present invention contains water, the viscosity of the composition (after 10 minutes at 37°C) that allows it to remain at the application site and release the active ingredient is preferably 190 to 800 Pa s, more preferably 200 to 500 Pa s. The viscosity of the composition after 10 minutes at 37°C can be measured using the same device as in the method for measuring the viscosity of the composition at 25°C described above.
[0033] When using the composition of the present invention, a desired amount is placed at a temperature close to body temperature (35°C to 42°C) either as is or after adding water as necessary. When the temperature of the composition reaches a temperature close to body temperature, the viscosity begins to increase, and the composition can remain at the application site for several minutes (3 to 10 minutes) and thicken to a viscosity that allows the active ingredient to be released for a long time. As a result, the composition of the present invention has the effect of being able to release the active ingredient for a long time and having little change in the release rate of the active ingredient even after a long time has passed (the effect of having excellent sustained release stability). The location with a temperature close to body temperature may be the application site (such as the oral cavity) or may be inside a device whose temperature is adjusted to about body temperature. EXAMPLES
[0034] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to these.
[0035] <Production of the compositions of Examples 1 to 41 and Comparative Examples 1 to 7> The temperature-sensitive polymer (X), the polymer compound (Y) having an anionic group or the cationic polymer (Y'), the water-soluble compound (Z), the component for adjusting the liquid property ("neutralizing component" in the table), and ion-exchanged water were mixed at 25°C to the concentration (wt %) shown in Table 1 to obtain the composition of each example.
[0036] <Description of each ingredient> The materials used in the examples and comparative examples are as follows. The viscosity at 25° C. of the polymer (X-5) and the polymer compound (Y) was measured using the same device as that used to measure the viscosity of the composition described below. [Temperature sensitive polymer (X)] (X-1): Methylcellulose [manufactured by Shin-Etsu Chemical Co., Ltd., degree of methoxy group substitution 1.8, viscosity of 2% by weight aqueous solution at 20°C is 4,000 mPa s] (X-2): Hydroxypropyl methylcellulose 60SH [manufactured by Shin-Etsu Chemical Co., Ltd., degree of methoxy group substitution 1.9, number of moles of hydroxypropyl group substitution 0.25 moles, viscosity of 2% by weight aqueous solution at 20°C is 4,000 mPa s] (X-3): Hydroxypropyl methylcellulose 65SH [manufactured by Shin-Etsu Chemical Co., Ltd., degree of methoxy group substitution 1.8, number of moles of hydroxypropyl group substitution 0.15 moles, viscosity of 2% by weight aqueous solution at 20°C is 4,000 mPa s] (X-4): Hydroxypropyl methylcellulose 90SH [manufactured by Shin-Etsu Chemical Co., Ltd., degree of methoxy group substitution 1.4, number of moles of hydroxypropyl group substitution 0.2 moles, viscosity of 2% by weight aqueous solution at 20°C is 4,000 mPa s] (X-5): N-isopropylacrylamide polymer [Sigma-Aldrich Co., Ltd., viscosity of 1% by weight aqueous solution at 25°C is 2,000 mPa s] [Polymer compound having an anionic group (Y)] (Y-1): Sodium carboxymethylcellulose [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., viscosity of 1% by weight aqueous solution at 25°C is 1,500 mPa s] (Y-2): Sodium polyacrylate [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., viscosity of 1% by weight aqueous solution at 25°C is 4,000 mPa s] (Y-3): Xanthan gum [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., viscosity of 1% by weight aqueous solution at 25°C is 1,500 mPa s] (Y-4): Sodium alginate [Kimika Co., Ltd., viscosity of 1% by weight aqueous solution at 20°C is 850 mPa s] [Polymer having a cationic group (Y')] (Y'-1): Polylysine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) [Water-soluble compound (Z)] (Z-1): Citric acid [FUJIFILM Wako Pure Chemical Industries, Ltd.] (Z-2): Malic acid [FUJIFILM Wako Pure Chemical Industries, Ltd.] (Z-3): Glutamic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (Z-4): Trisodium phosphate pentasodium (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (Z-5): Sodium hexametaphosphate [(NaPO3)m, m: 10 to 23, mixture of compounds with molecular weights of 1019.6 to 2345.1, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.] (Z-6): Sodium pentapolyphosphate [Na7P5O 16 , molecular weight 571.78, manufactured by Taihei Chemical Industry Co., Ltd.] (Z-7): Short-chain sodium polyphosphate [number average molecular weight 1489.4, average chain length 14, manufactured by Regenetis Co., Ltd.] (Z-8): Medium-chain sodium polyphosphate [number average molecular weight 6179.7, average chain length 60, manufactured by Regenetis Co., Ltd.] (Z-9): Long-chain sodium polyphosphate [number average molecular weight 13317.0, average chain length 130, manufactured by Regenetis Co., Ltd.] [Neutralizing ingredient] (N-1): Citric acid monohydrate [FUJIFILM Wako Pure Chemical Industries, Ltd.] (N-2): 30% by weight ammonia water
[0037] [Viscosity measurement of composition] The viscosities of the compositions of the Examples and Comparative Examples were measured by the following method, and the results are shown in Table 1. (Measurement conditions) Equipment: MCR92 (Anton Paar) Fixture: PP-25 (parallel plate with a diameter of 25 mm) Gap: 1mm Temperature: 25℃ or 37℃, -Distortion rate: 0.1 1 / s (Rotation speed: 0.11 rpm)
[0038] (Measurement method) (1) Measurement of composition viscosity at 25°C Approximately 1.0 g of each composition was placed on the sample stage and sandwiched with PP-25, the distance between the parallel plates was 1 mm, and the protruding sample was scraped off. After regulating the temperature at 25°C for 1 minute, the viscosity value at a rotation speed of 0.11 rpm was recorded. This viscosity was taken as the viscosity at 25°C. The results are shown in Tables 1 and 2. (2) Measurement of composition viscosity at 37°C The sample (1) was left as it was on the sample stage, and the temperature was raised to 37°C. After 3 minutes of temperature control at 37°C, the viscosity value was recorded at a rotation speed of 0.11 rpm (viscosity at 37°C for 3 minutes). After 7 minutes of temperature control at 37°C, the viscosity value was recorded at a rotation speed of 0.11 rpm (viscosity at 37°C for 10 minutes). The results are shown in Tables 1 and 2.
[0039] [Evaluation of the stability of the composition] The compositions of the Examples and Comparative Examples were each left to stand in an incubator at 25°C for 30 days, and the presence or absence of changes from the initial state of the composition (state before standing) was visually confirmed. The stability evaluation results were evaluated based on the following evaluation criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ○: No change was observed (no problem in use). Δ: The composition became cloudy, but no decrease in fluidity was confirmed (no problem in use). ×: The composition became cloudy and a clear decrease in fluidity was confirmed (problems may occur in use).
[0040] [Evaluation of sustained release] (1) Evaluation of sustained release properties of the compositions of Examples 1 to 32 and Comparative Examples 1 to 7 1 g of each composition of the examples was dispensed into each well of a 12-well plate. 1 mL of ion-exchanged water was added to each 12-well plate, and the plate was left to stand at 37°C to start the sustained release test. After the start of the test, the entire amount of the supernatant was collected every 30 minutes, and 1 mL of ion-exchanged water was added to each well again to continue the sustained release test. This operation was continued for 6 hours. The concentrations of compound (Z) in the collected supernatants at 1, 2, 3, 4, 5, and 6 hours were quantified using the kit described below, and evaluated according to the following evaluation criteria. The quantitative concentration results and evaluation results are shown in Tables 1 to 3. The unit of concentration is "mmol / L". In the table, "6h concentration / 1h concentration" means "concentration ratio (concentration of compound (Z) at 6 hours / concentration of compound (Z) at 1 hour)". (Kit used) Citric acid: EnzyChrom Citrate Assay Kit (Bioassay systems) Malic acid: Malate Assay Kit (Cell Bio Labs) Glutamate: Glutamate Assay Kit (Cell Bio Labs) Polymeric phosphate: PiBlue Phosphate Assay Kit (Bioassay systems) (Evaluation Criteria) In the examples where the amount of compound (Z) is 3% by weight (Examples 1 to 10, 13 to 26, 29 to 32, Comparative Examples 1 to 7), if the concentrations of compound (Z) in the supernatants recovered after 1, 2, 3, 4, 5, and 6 hours are 3.9 mmol / L or more, respectively, and the concentration ratio (concentration of compound (Z) after 6 hours / concentration of compound (Z) after 1 hour) is 0.5 or more, the sustained release stability is determined to be excellent. In the case where the amount of compound (Z) is 0.1% by weight (Examples 11 and 27), if the concentrations of compound (Z) in the supernatants collected after 1, 2, 3, 4, 5, and 6 hours are 0.13 mmol / L or more, respectively, and the concentration ratio (concentration of compound (Z) after 6 hours / concentration of compound (Z) after 1 hour) is 0.5 or more, the active ingredient can be released for a long time, and there is little change in the amount released even after a long time has passed (the change in the release rate of the active ingredient is small), so it is determined that the sustained release stability is excellent. In the example (Example 12) in which the amount of compound (Z) is 1% by weight, if the concentrations of compound (Z) in the supernatants recovered after 1, 2, 3, 4, 5, and 6 hours are 1.3 mmol / L or more, respectively, and the concentration ratio (concentration of compound (Z) after 6 hours / concentration of compound (Z) after 1 hour) is 0.5 or more, the active ingredient can be released for a long time, and there is little change in the amount released even after a long time has passed (the change in the release rate of the active ingredient is small), so it is determined that the sustained release stability is excellent. In the example (Example 28) in which the amount of compound (Z) is 4% by weight, if the concentrations of compound (Z) in the supernatants collected after 1, 2, 3, 4, 5, and 6 hours are 5.2 mmol / L or more, respectively, and the concentration ratio (concentration of compound (Z) after 6 hours / concentration of compound (Z) after 1 hour) is 0.5 or more, the active ingredient can be released for a long time, and there is little change in the amount released even after a long time has passed (the change in the release rate of the active ingredient is small), so it is determined that the sustained release stability is excellent. . The closer the concentration ratio (concentration of compound (Z) at 6 hours / concentration of compound (Z) at 1 hour) is to 1, the smaller the change in the amount of active ingredient released is even after a long period of time, which is preferable.
[0041] (2) Evaluation of sustained release properties of the compositions of Examples 33 to 41 1 g of each composition was dispensed into each well of a 12-well plate, 1 mL of ion-exchanged water was added to each 12-well plate, and the plate was left to stand at 37°C for 10 minutes before starting the sustained release test. After the start of the test, the entire amount of the supernatant was collected every 30 minutes, and 1 mL of ion-exchanged water was added to each well again to continue the sustained release test. This operation was continued for 6 hours. The concentrations of the substance (Z) in the collected supernatants at 1, 2, 3, 4, 5, and 6 hours were quantified using the same kit as in (1). Evaluation was performed according to the following evaluation criteria. The quantitative concentration results and evaluation results are shown in Table 4. The unit of concentration is "mmol / L". (Evaluation Criteria) If the concentrations of compound (Z) in the supernatants collected at 1, 2, 3, 4, 5, and 6 hours were 3.9 mmol / L or more, respectively, and the concentration ratio (concentration of compound (Z) at 6 hours / concentration of compound (Z) at 1 hour) was 0.5 or more, the active ingredient was released for a long period of time, and there was little change in the amount released even after a long period of time had passed (there was little change in the release rate of the active ingredient), so it was determined that the sustained release stability was excellent. The closer the concentration ratio (concentration of compound (Z) at 6 hours / concentration of compound (Z) at 1 hour) is to 1, the smaller the change in the amount of active ingredient released even after a long period of time, and therefore the more preferable it is.
[0042] [Table 1]
[0043] [Table 2]
[0044] [Table 3]
[0045] [Table 4]
[0046] As shown in Tables 1 and 2, it was confirmed that Examples 1 to 32, which contain a temperature-sensitive polymer (X), a polymer compound (Y) having an anionic group, and a water-soluble compound (Z) and have a ratio of the weight of (Y) to the weight of (Z) of 0.025 to 20, have good storage stability at 25°C and excellent sustained release stability. On the other hand, all of the Comparative Examples had inferior sustained release stability compared to the Examples (see Table 3). Furthermore, as shown in Table 4, it was confirmed that Examples 33 to 41, which were previously allowed to stand at 37°C for 10 minutes to thicken, also had excellent sustained release stability, similar to Examples 1 to 32. From this result, it was found that the active ingredient can be sustainedly released to the application site for a long period of time even if the product was previously thickened and then placed on the application site. From the above, it can be seen that the present invention can provide a composition for sustained release materials having excellent sustained release stability.
Claims
1. A composition comprising a temperature-sensitive polymer (X), a polymer compound (Y) having an anionic group, and a water-soluble compound (Z) having a number average molecular weight of 100 to 15,000, the weight Wy of the polymer compound (Y) having an anionic group; The ratio (Wy / Wz) of the weight of the water-soluble compound (Z) to the weight Wz of the water-soluble compound (Z) is 0.025 to 20.
2. 2. The composition for sustained release material according to claim 1, wherein the temperature-sensitive polymer (X) is at least one member selected from the group consisting of N-isopropylacrylamide polymers, methylcellulose, and hydroxyalkylmethylcellulose.
3. The composition for sustained release material according to claim 1 or 2, wherein the ratio [Wx / (Wy+Wz)] of the weight Wx of the temperature-sensitive polymer (X) to the total weight of the weight Wy and the weight Wz is 0.08 to 45.
Citation Information
Patent Citations
Aqueous gel composition
JP1986192750A
Temperature-sensitive fine particle composition and temperature-sensitive fine particle sheet
JP2003147210A
Thickener and cosmetic and cleaner containing the same
JP2007217348A
Polymer hydrogel and method for preparing the same
JP2010535911A
Coated composite material
WO2017170927A1